2022
DOI: 10.1007/s40615-022-01298-3
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionate Burden of COVID-19 Cases among Arab Americans

Abstract: Racial and ethnic disparities in COVID-19 cases are pervasive. Some minority, immigrant, and marginalized groups, such as Arab Americans, have been excluded from the research. This population confronts barriers to health care, discrimination, and other factors that may affect understanding, testing, and treatment as it relates to COVID-19. Arab Americans are unique compared to Hispanic, non-Hispanic black, and Asians because Arab Americans do not have a specific ethnic identifier and are classified as non-Hisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As findings by Dallo et al (2022) revealed the disproportionate number of COVID-19 cases among Arab Americans compared to other racial–ethnic minority groups, including this group in discourse on health disparities is clearly indicated. Future researchers should continue engaging with the Arab American community to understand the reasons for these health disparities and to identify interventions that can alleviate such disparities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As findings by Dallo et al (2022) revealed the disproportionate number of COVID-19 cases among Arab Americans compared to other racial–ethnic minority groups, including this group in discourse on health disparities is clearly indicated. Future researchers should continue engaging with the Arab American community to understand the reasons for these health disparities and to identify interventions that can alleviate such disparities.…”
Section: Discussionmentioning
confidence: 98%
“…As Arab Americans have largely been invisible from public health discourse (Dallo et al, 2022), it is crucial that researchers do not overlook their experiences as doing so will only further limit the availability of adequate interventions for this vulnerable population. The present findings elucidate experiences unique to Arab Americans during the COVID-19 pandemic.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on health behaviors especially vaccination trends among MENA population in the US lags as compared to other immigrant and minority groups [21][22][23]. Only a few studies have examined COVID-19 vaccine hesitancy among Arab Americans [20,24,25,26], with the focus areas primarily being Michigan, Minnesota, California, New York and Virginia as the most frequent research sites for examining MENA health trends [27]. This cross-sectional study aimed at understanding the predictors of COVID-19 vaccination among MENA individuals focused on Harris County and Fort Bend MENA residents.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, adults who reported at least 1 of 43 Arab ancestries located in the Middle East or were born in Comoros, Djibouti, or United Arab Emirates were included. 14 - 18 To obtain a more inclusive representation of MENA individuals, we also included individuals who were born in the following MENA countries; Iran, Iraq, Israel, Jordan, Kuwait, Lebanon, Saudi Arabia, Syria, Turkish, Yemen, Algeria, Egypt, Libya, Morocco, Somalia, and Tunisia. Race, ethnicity, place of birth and ancestry were combined to create four categories: US-born non-Hispanic White; foreign-born non-Hispanic White; US-born MENA, and foreign-born MENA.…”
Section: Methodsmentioning
confidence: 99%